Perilaku Antisosial pada Fandom Peer Attachment dan Celebrity Worship - Rini Zahraini Nurajmi; Ikhwan Lutfi; Moh. Irvan (Universitas Kristen Maranatha, 2025)
The aim of this research is to explore whether peer attachment, celebrity worship, age, and gender have an impact on antisocial behavior within fandom (Korean music fans). This study employs a predictive correlational design using regression analysis techniques for data analysis. Antisocial behavior is the dependent variable, while the independent variables are peer attachment, celebrity worship, age, and gender. The sample consists of 325 individuals, including 61 males (18.8%) and 264 females (81.2%). The sample age range is 15-30 years (M=21.88; SD=2.69). The sampling technique used is non-probability sampling, specifically convenience sampling. Data collection was carried out using a likert-type questionnaire. The Subtypes of Antisocial Behavior Questionnaire (STAB) by Burt and Donnellan (2009) was used to measure antisocial behavior, peer attachment was measured using the Inventory of Parent and Peer Attachment (IPPA) by Armsden and Greenberg (1987), and the Celebrity Attitude Scale (CAS) by Maltby et al. (2006) was used to measure celebrity worship. The validation of measurement instruments was conducted using Confirmatory Factor Analysis (CFA). The results of multiple regression analysis indicate that the dimensions with a significant impact are peer trust, peer alienation, intense-personal, borderline-pathological, and gender. Meanwhile, peer communication, social entertainment, and age do not have a significant impact on antisocial behavior within fandom.